Facile synthesis and self-cleaning application of bimetallic (CuSn, CuNi) dendrites - Biswas, Anupam; Kulkarni, Mayuresh A.; Bakthavatsalam, Rangarajan; Mondal, Sourik K.; Dwivedi, Pravin K.; Shelke, Manjusha V.; Devi, Radhamonyamma N.; Banpurkar, Arun G.; Kundu, Janardan (Chemistryselect, 2017)
Bimetallic dendrites (Au, Ag, Pt, Pd) have received intense research interest due to their applications in catalysis and sensing. However, reports on rational synthesis of non-noble bimetallic dendrites that finds self-cleaning applications are scanty. Here, we demonstrate one step co-reduction based galvanic replacement reaction (GRR) for synthesis of alloyed bimetallic dendrites (CuSn, CuNi) with controlled surface roughness and chemical composition. Probing their growth process reveals that i) for CuSn dendrites, co-reduction of Cu2+ and Sn2+ is observed throughout GRR; ii) for CuNi dendrites, Cu nanoparticle, that deposits initially, augments the reduction of Ni2+ which leads to CuNi alloy phase formation during later stages of GRR. These dendrites, naturally having dual degree of surface roughness (micro/nano), have been exploited here for fabricating superhydrophobic surfaces (SHS) with excellent self-cleaning abilities. They show enabling properties such as high contact angle, minimal contact angle hysteresis, and excellent Cassie state stability with no impalement. They maintain superhydrophobicity when exposed to different environmental conditions (low temperature, high temperature, exposure to corroding solutions and UV radiation). The present facile methodology for fabrication of bimetallic dendrites is beneficial for low-cost production of functional nano/micro-materials.

Aqueous dispersions of lipid nanoparticles wet hydrophobic and superhydrophobic surfaces - Kumar, Manoj; Kulkarni, Mayuresh A.; Chembu, Narendiran G.; Banpurkar, Arun; Kumaraswamy, Guruswamy (Soft Matter, 2018)
Efficient delivery of aqueous sprays to hydrophobic surfaces is the key technological challenge in a wide variety of applications, including pesticide delivery to plants. To account for losses due to bouncing of pesticide sprays off hydrophobic leaf surfaces, a large excess of pesticide is typically employed, resulting in environmentally hazardous run-offs that contaminate soil and ground water. We demonstrate that aqueous dispersions of glycerol monooleate nanoparticles, called cubosomes, wet hydrophobic and superhydrophobic surfaces and adhere to them. Cubosomes comprise glycerol monooleate lipid molecules self-assembled into a double diamond cubic phase, that form stable aqueous dispersions that are sterically stabilized using amphiphilic block copolymers. We use high speed imaging to monitor the spreading and retraction of aqueous drops impinged on model hydrophobic substrates and on superhydrophobic lotus leaves. We show that cubosomes diffuse to hydrophobic substrates and reorganize to form a thin, approximate to 2 nm adsorbed lipid layer during the millisecond time scales that characterize drop impact. This adsorbed film drastically reduces the water contact angle, transforming the hydrophobic surface to hydrophilic, thus facilitating retention of the aqueous drop on the surface. Aqueous drops of cubosomes impinged at low velocities on inclined natural superhydrophobic lotus leaf surfaces do not roll off, unlike drops of water or surfactant solutions. When sprayed on inclined lotus leaves, corresponding to the case of high velocity drop impingement, cubosome dispersions form a continuous wetting film. Our results have important implications for efficient, environment-friendly delivery of pesticide sprays.